Marigold flower like structured Cu2NiSnS4 electrode for high energy asymmetric solid state supercapacitors - Isacfranklin, M. (2021)
The growth in energy devices and the role of supercapacitors are increasingly important in today’s world. Designing an electrode material for supercapacitors using metals that have high performance, superior structure, are eco-friendly, inexpensive and highly abundant is essentially required for commercialization. In this point of view, quaternary chalcogenide Cu2NiSnS4 with fascinating marigold flower like microstructured electrodes are synthesized using different concentrations of citric acid (0, 0.05 M, 0.1 M and 0.2 M) by employing solvothermal method. The electrode materials physicochemical characteristics are deliberated in detail using the basic characterization techniques. The electrochemical studies revealed better electrochemical performances, in particular, Cu2NiSnS4@0.1 M-CA electrode revealed high 1029 F/g specific capacitance at 0.5 A/g current density. Further, it retained 78.65% capacity over 5000 cycles. To prove the practical applicability, a full-cell asymmetric solid-state device is fabricated, and it delivered 41.25 Wh/Kg and 750 Wh/Kg energy and power density at 0.5 A/g. The optimum citric acid added Cu2NiSnS4 electrode is shown to be a promising candidate for supercapacitor applications.